Krajobrazowe opisy i pejzaż w korespondencjach Franciszka Bahuszewicza publikowanych w tygodniku „Kraj” - Rudziewicz, Irena (Acta Polono-Ruthenica, 2006)
In this article, focusing herself on the selected publicist texts by Franciszek Bahuszewicz, the authoress drew her attention to the role and significance of the descriptions of nature, its landscapes and the surrounding reality. The motifs and issues connected with nature and included in the correspondence helped to emphasize varied experiences in a particular period of time, in a concrete geographical sphere.